Preparation of Zeolite X by the Aluminum Residue From Coal Fly Ash for the Adsorption of Volatile Organic Compounds - Zhu, Tao; Zhang, Xing; Han, Yiwei; Liu, Tongshen; Wang, Baodong; Zhang, Zhonghua (Frontiers in Chemistry, 2019)
In China, coal fly ash is a large-scale solid waste generated by power plants. The high value utilization of coal fly ash has always been a hot research issue in China for these years. In this paper, the synthesis of zeolite X using aluminum residue from coal fly ash can not only realize the resource utilization of waste, but also achieve the effect of energy saving and emission reduction. Zeolite X prepared by hydrothermal synthesis method have been found to have higher purity and better crystallinity by chemical composition analysis. By comparing and analyzing the adsorption performance of zeolite X and activated carbon on volatile organic compounds, it is found that the adsorption capacity of zeolite X is higher than that of activated carbon, and it has stronger stability. This indicates that the zeolite X synthesized by this environmentally friendly and economical method has a good application prospect in adsorbing volatile organic compounds.